PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DAN GAYA KOGNITIF TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII MADRASAH TSANAWIYAH - Hikmawati, Hikmawati; kamid, Kamid; Syamsurizal, Syamsurizal (Program Magister Teknologi Pendidikan Universitas Jambi, 2013)
This is a quasi-experimental study (Quasi-Experimental Design) nonequivalent control group design with applying 3 Ã— 2 factorial design. Subjects were students MTs Laboratory Fak. Tarbiyah IAIN STS Jambi City class VIII semester of academic year 2012/2013. Data collection was conducted by using two different instruments namely instruments Group Embedded Figures Test (GEFT) to measure cognitive styles. Instrument in the form of students and students' mathematics achievement test form of objective questions (multiple choice). Hypotheses were tested using analysis of Varian Two Line (Two-Way ANOVA), after testing prerequisites are met ie the data are normally distributed and the variance between relatively homogeneous sample. From the data analysis and statistical test results obtained are: (1) there is the influence of media use on learning outcomes of mathematics teaching eighth grade students of MTs, (2) there is an influence of cognitive style on learning outcomes of students' mathematics class VIII MTs (and (3) there is no significant interactions between media learning and cognitive style on learning outcomes of students' mathematics class VIII MTs Keyword: interactive cd, powerpoint, konvensional, cognitive style and learning outcomes